1990
DOI: 10.1007/bf00058158
|View full text |Cite
|
Sign up to set email alerts
|

Effects of glycosaminoglycans and extracellular matrix components on metastatic rat rhabdomyosarcoma tumor and myoblast cell proliferation

Abstract: Experiments were performed to determine the relative effects of glycosaminoglycans and extracellular matrix components alone or in association with various substrates, including extracellular matrix, on the proliferation of rat rhabdomyosarcoma (RMS) cell lines of different metastatic potential and nontumorigenic rat myoblast L6 cells. The assays used various substrates: tissue culture plastic, type I and IV collagen, fibronectin, laminin and extracellular matrix deposited by corneal endothelial cells. In cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1993
1993
2020
2020

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…These GAGs have been shown to be synthesized by several myogenic cell lines in vitro. 45, 46 They are involved in the regulation of growth factor activity and indeed, have been shown to stimulate proliferation of myoblasts of cell line 6 when added in the culture medium 47. Each of these molecules stimulated satellite cell proliferation to a maximum of 130% in the presence of 0.1 μg/mL KS (about 1 n M ) or HS (about 2 n M ), or 1 μg/mL DS (about 26 n M ), assuming that molecular masses of KS, HS, and DS are 109, 50, and 38 kDa, respectively 48…”
Section: Resultsmentioning
confidence: 99%
“…These GAGs have been shown to be synthesized by several myogenic cell lines in vitro. 45, 46 They are involved in the regulation of growth factor activity and indeed, have been shown to stimulate proliferation of myoblasts of cell line 6 when added in the culture medium 47. Each of these molecules stimulated satellite cell proliferation to a maximum of 130% in the presence of 0.1 μg/mL KS (about 1 n M ) or HS (about 2 n M ), or 1 μg/mL DS (about 26 n M ), assuming that molecular masses of KS, HS, and DS are 109, 50, and 38 kDa, respectively 48…”
Section: Resultsmentioning
confidence: 99%
“…In this case, an investigation of their functional activity in vitro and in vivo is facilitated due to the existence of various technical tools (specific primers, antibodies etc). Another approach is to isolate different classes of glycosaminoglycans (HS, DS, CHS, KS, HA) and investigate their influence on cell proliferation in tissue culture (Redini et al 1990;Volpi et al 1994;Nikitovic et al 2005;Nagasawa et al 1993;Maurer et al 1994). However due to a high heterogeneity of polysaccharide chains GAG even within the same PG class, very careful attention should be paid to the problem of a sameness of PG/GAG samples.…”
Section: Discussionmentioning
confidence: 99%
“…Different glycosaminoglycans were tested to evaluate their effects on proliferation of various cell lines. It was shown that heparin (He) is able to inhibit cell proliferation, while chondroitin sulfates (CS) and dermatan sulfates (DS) significantly stimulate cell growth of rhabdomyosarcoma (RMS) (Redini et al 1990) and monoblastic leukemia cell line (U-937) (Volpi et al 1994). However for osteoblastic cell lines, an inhibitory effect of CS and DS was shown (Nikitovic et al 2005).…”
Section: Introductionmentioning
confidence: 99%